Pengukuran Risiko Keamanan Aset TI Menggunakan Metode FMEA dan Standar ISO/IEC 27001:2013 - Munaroh, Lailatul; Amrozi, Yusuf; Nurdian, Risky Agung (Technomedia Journal, 2021)
Information technology is now a top priority because of its effectiveness and efficiency. However, with the ease and effectiveness of technology that is vulnerable to its security. For this reason, security management is also a priority after the existence of information technology / information systems. This study aims to measure and identify risks using the FMEA method and ISO / IEC 27001: 2013 standard. The analysis shows that there are 22 cause failures that will cause a risk to the security of IT assets in the Domestic Trade (PDN) Department of Trade and Industry of the XYZ Provincial Government. There are 11 cause failures that have a high level with a vulnerable value of 400 - 175.